Development of a clinically relevant ex vivo model of cardiac ablation for testing of ablation catheters. (26th December 2022) - Lacko, Christopher S.; Chen, Qi; Mendoza, Vivienne; Parikh, Vanessa; Eichenbaum, Gary; Bar‐Tal, Meir; Eckert, Chad E.; De Leon, Hector; Matonick, John P.; Sharma, Tushar
Abstract: Introduction: Reliable ex vivo cardiac ablation models have the potential to increase catheter testing throughput while minimizing animal usage. The goal of this work was to develop a physiologically relevant ex vivo swine model of cardiac ablation displaying minimal variability and high repeatability and identify and optimize key parameters involved in ablation outcomes. Methods and Results: A root cause analysis was conducted to identify variables affecting ablation outcomes. Parameters associated with the tissue, bath media, and impedance were identified. Variables were defined experimentally and/or from literature sources to best mimic the clinical cardiac ablation setting. The model was validated by performing three independent replicates of ex vivo myocardial ablation and a direct comparison of lesion outcomes of the ex vivo swine myocardial and in vivo canine thigh preparation (TP) models. Replicate experiments on the ex vivo model demonstrated low variance in ablation depth (6.5 ± 0.6, 6.3 ± 0.6, 6.2 ± 0.4 mm) and width (10.4 ± 1.1, 9.7 ± 1.0, 9.9 ± 0.9 mm) and no significant differences between replicates. In a direct comparison of the two models, the ex vivo model demonstrated ablation depths similar to the canine TP model at 35 W (6.9 ± 1.0, and 7.0 ± 0.9 mm) and 50 W (8.0 ± 0.7, and 8.4 ± 0.7 mm), as well as similar power to depth ratios (15% and 19% for the ex vivo cardiac and in vivo TP models, respectively). Conclusion: The ex vivo model exhibited strong lesion reproducibility and power‐to‐depth ratios comparable to the in vivo TP model. The optimized ex vivo model minimizes animal usage with increased throughput, lesion characteristics similar to the in vivo TP model, and ability to discriminate minor variations between different catheter designs. Abstract : Central Illustration: Root cause analysis‐based identification and optimization of parameters influencing cardiac ablation outcomes. The model parameters (root causes) were categorized into those affecting the ex vivo tissue, the bath media, and the system impedance. The effects of each parameter were evaluated and constrained (specific actions) to best mimic the clinical cardiac ablation environment. The multistep, systematic process resulted in a tightly controlled ex vivo model able to generate consistent and repeatable ablation lesions, and reliable lesion dimensional data.